Capital formation, capital rate of return and economic inequality in Middle East and North Africa - Farid, Marmar (AUC Knowledge Fountain, 2016)
Economic inequality is turning into one of the most pressing issues in the 21st century. The inequality gap between the rich and the poor raises red flags to the world's economic, social and political well-being. A small minority is controlling the world's economy and has the most influential power, which will result in more political instability and lower social inclusion within the world. This was witnessed by the reasons studied behind the rise of the Arab Spring and the turmoil in the MENA region. The literature exhibits a wealth of studies and ongoing debate for the reasons behind inequality among and within the countries in the world. However, there is a dearth in literature on MENA Region when it comes to analyzing the causes leading to inequality and the factors that determine its level in the region, with an emphasis on the effect of the capital and the rate of returns. This study analyzed panel data from 1963 to 2012 for MENA countries to empirically investigate the effect of the capital formation, rate of returns on capital, controlling for the economic growth and natural resources rent on economic inequality in MENA. The empirical results showed that that the factors used to measure the capital formation such as Gross Domestic Savings and Gross Fixed Capital Formation are positively related to economic inequality and hence heighten the inequality gap. Conversely, the factors used to measure the capital rate of returns such as the real interest and the deposit interest rate are negatively related to economic inequality. When the deposit interest rate increases, the economic inequality decreases. Policy recommendations are made to develop comprehensive strategies for inclusive development and better wealth distribution. Revised fiscal and monetary policies to reform tax and benefits are needed to increase fair and re-distributive effects and avoid the effect of capital and power accumulation.